Artificial intelligence applied to stakeholder theory - Montez, Ana Rita Henriques (2022)
The constant evolution and change in the world have forced organizations to rethink their business model. Intelligent Systems have proved to be very promising in business management, increasing business performance by simplifying processes, increasing efficiency and decision-making. The importance of Stakeholder Theory as an integral part of business analysis becomes evident as all Stakeholders will influence the business environment at some point, and therefore its constant monitoring becomes crucial. Despite the importance of stakeholder analysis, it remains a significant gap in organizations. To find solutions to this problem, this investigation's main objective is to study the impact of Intelligent Systems on Stakeholder Theory. For this, after a literary review, two research questions were raised. The investigation is based on an inductive, exploratory study and was carried out from a non-probabilistic convenience sample. To obtain answers to the research questions, a hybrid approach of qualitative and quantitative methods was used, with an analysis of 13 interviews and 168 online questionnaires, respectively. The results obtained allow us to demonstrate that the use of Intelligent Systems related to the Stakeholder Theory in organizations becomes relevant and that the perception and knowledge of individuals, influenced or not by the benefits and challenges that the implementation of Artificial Intelligence can entail, becomes crucial in the decision to implement these systems in their companies.